The Power of Predictions: An Emerging Paradigm for Psychological Research - Hutchinson, J. Benjamin; Barrett, Lisa Feldman (Current directions in psychological science : a journal of the American Psychological Society, 2019)
In the last two decades, neuroscience studies have suggested that various psychological phenomena are produced by predictive processes in the brain. When considered together, these studies form a coherent, neurobiologically inspired program for guiding psychological research about the mind and behavior. In this article, we consider the common assumptions and hypotheses that unify an emerging framework and discuss the ramifications of such a framework, both for improving the replicability and robustness of psychological research and for renewing psychological theory by suggesting an alternative ontology of the human mind.